Synthesis, Structural Characterization，DFT，Hirschfeld Surface and Catalytic Activity of a New Zn (II) Complex of 4-Acetylbenzoic Acid - Li-Hua Wang; Hao-Wen Tai (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
A new Zn(II) complex of 4-acetylbenzoic acid, namely  [ZnL2(H2O)2] (1) (HL = 4-acetylbenzoic acid) has been synthesized in water-ethanol (v:v = 1:2) solution using zinc acetate dihydrate, 4-acetylbenzoic acid, and NaOH as reactants. The structure of complex (1) has been characterized by IR and X-ray single-crystal diffraction. X-ray diffraction analysis of complex (1) reveals that the Zn(II) ion is six-coordinated in a distorted octahedral coordination geometry with four carboxylic O atoms from two different bidentate 4-acetylbenzoic acid ligands (O1, O2, O1a, O2a) and two O atoms from two coordinated water molecules (O4 and O4a). Complex (1) forms 1D chained structure by the intermolecular and intramolecular O-H···O hydrogen bonds, and further forms a three-dimensional network structure by the π-π interaction of benzene rings and intermolecular O-H···O hydrogen bonds. The singlet ground-state geometry of the complex (1) were optimized using the PBE0 functional. The intermolecular interactions of complex (1) were quantitatively analysed by 3D Hirschfeld surface analysis and associated 2D fingerprint plots. The catalytic activity of complex (1) has been tested for the oxidation of benzyl alcohol under O2 atmosphere. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).